(untitled) (World Bulletin of Social Sciences, 2023)
This article delves into the social psychological aspects that contribute to the formation of attitudes toward educational activities in primary education. The study explores the importance of attitudes in shaping a child’s educational experience, discusses various factors influencing attitude formation, presents research methods employed, presents empirical findings, engages in a discussion of the results, and offers conclusions and suggestions for educators, parents, and policymakers.